MENGUNGKAP KEBUNGKAMAN DALAM PRODUKTIVITAS FIKSI POP ISLAMI PENERBIT MIZAN - Cucum Cantini (POETIKA, 2017)
This research focus on the discourse of Syiah that alleged to Mizan over the first publication of Dialog Sunni-Syiah which published at 1983. Despite of that negative justification, Mizan publisher still exist and productive, especially for producing pop-islamic fiction. By using Pierre Macherey’s literary production theory, spoken and unspoken, then found a ideological islamization project and also an anti-western effort in the other pop-islamic fiction by realizing it through figuration and symbol inside the text; hidayah, islam figure, moslem gathering, ideal by wearing hijab, Arabian’s figure domination, history of islamic resistance, and preferring middle east background. Therefore, unconsciously, pop-islamic fiction reducing the negative image of Mizan as pop-islamic publisher as well as showing the existence of islamic power. Mizan’s presence appears because of the enthusiasm of intellectuals to the islamic ideas books, especially about Islam Iran Revolution at 1979. By the sensitivity of the discourse in Orde Baru era, then Mizan publisher be a  part of negative image in islam. By the Mizan’s productivity producing pop books then the more the image faded, simultaneously awaken islamic power in Indonesia’s popular culture.Keywords: Pop-islamic fiction, Mizan Publisher, spoken and unspoken , silences